Knowledge and Power in Dan Brown’s the Lost Symbol - Ayoub BENTOMI.Rabeh Imad Eddine OUADOUD, Mrs. Nassima AMIROUCHE (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
ABSTRACT The detective novel is one of the most prominent examples occupying the discussion arena today, as the American detective novels have spread all over the world. It was able to master the features of excitement and suspense to achieve its universality. Dan Brown is one of the American authors, who wrote well-researched novels that centered on the secret organizations and the conflict between science and religion and had intricate plots. He was best known for the Robert Langdon series, which notably included The Lost Symbol, which is the essence of this study. Hence, this thesis aims to unveil an important aspect of the study, which is highlighting some aspects of power and knowledge with accordance to the theory of Michel Foucault discussed in Dan Brown‘s The Lost Symbol. Added to this, this study aims at discovering Freemasonry as a religion related to Christianity, its symbols, and its existence in the Washington DC historical buildings as revealed in the novel. This thesis is entitled: “Knowledge and Power in Dan Brown’s the Lost Symbol”.
Keywords: Key words: The Detective Novel, the Lost Symbol. Knowledge, Power, Freemasonry